Understanding the risk of enhanced particle penetration into slow sand filter beds when using underwater skimming techniques - Elemo, Tolulope; Chipps, Michael; Graham, Nigel; Turner, Andrew; Jefferson, Bruce; Hassard, Francis (Elsevier, 2025)
This study evaluated abiotic slow sand filters (SSFs) to understand the risk of particle penetration during underwater skimming (UWS), focusing on clogging, headloss development, and particle breakthrough. Pilot-scale filters containing clean sand were challenged with dispersed kaolin particles to simulate surface accumulation, and the sand surface was agitated to mimic UWS procedures. The study was undertaken with no maturation period to consider the worst-case scenario corresponding to the period just after filter skimming. Agitating the surface and restarting flow released captured particles, some moving downward through the filter. Shallow filter depths resulted in particles appearing in the filtrate, but increasing the media depth beyond 500 mm minimized this effect. Since 90 % of headloss occurred in the upper layers, deeper particle penetration was insignificant. Increasing the hydraulic loading rate from 0.3 to 0.5 m/h reduced particle retention by 0.72 log, yet all abiotic SSFs achieved over 2 log particle capture. Small particles (2–10 μm) were removed by 2 logs, indicating sufficient non-viral pathogen retention under routine conditions. Effective capture of particles sized 2–125 μm suggested minimal risk to water quality and public health during UWS on full-scale SSFs. Using clean sand and kaolin represented a worst-case scenario, excluding biological maturation and particles. The findings suggest that under normal conditions, UWS does not increase deep particle penetration or breakthrough, supporting its safe implementation to enhance filter maintenance without compromising water quality.
Keywords: Particle penetration; Slow sand filter (SSF); Underwater skimming (UWS); Water treatment